The MESSAGE OF MORAL VALUES IN THE FILM "GUBANG THE MOVIE": Introduction, Method, Results and Discussion, conclusion - Wiwik Swastiwi, Anastasia; Tety Kumalasari; Zaitun (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2022)
Abstract Gubang is a traditional art of the Malay community on Jemaja Island. In the past, Gubang was a game played by the spirits of the Bunian people. The art of Gubang was later made into a film titled "Gubang The Movie" by Sarman Galang. This film was produced in 2015 by Tuah Production with a drama genre with a duration of 95 minutes. The film titled "Gubang The Movie" by Sarman Galang as a medium in conveying messages through story plots conveyed by the screenwriter to the audience. Film has a function to be able to convey messages in the form of information, education, and entertainment. This paper discusses the moral messages and values ​​in the film titled "Gubang The Movie" by Sarman Galang. The method used in this study is a descriptive method, namely describing the data by analyzing the data according to the reality as it is about the moral values ​​contained in a film titled "Gubang The Movie" by Sarman Galang. Based on the film "Gubang The Movie" there is a moral message that contains a symbol of identity consisting of the value of patience, the value of persistence, the value of courage, and the value of kindness. Keywords: Gubang, message, value, moral, symbol, identity